Changes in the geopotential height at 500 hPa under the influence of external climatic forcings. Issue 24 (19th December 2015) - Christidis, Nikolaos; Stott, Peter A.
Abstract: Apart from global scale surface warming, anthropogenic forcings also lead to warming and thermal expansion of the lower atmosphere. Here we investigate these effects using the geopotential height at 500 hPa, an indicator of the combined thermodynamic and dynamic climatic response to external forcings. We employ optimal fingerprinting, which uses information from reanalysis data sets and experiments with seven state‐of‐the‐art climate models, to assess the role of anthropogenic and natural influences on changes in the geopotential height during the satellite era. A significant global increase in the annual and seasonal mean geopotential height due to human influence is detected, a result confirmed with four different reanalysis data sets. A more moderate increase in the annual mean associated with natural forcings is also detected. Our findings, consistent with previous detection and attribution studies of changes in temperature and sea level pressure, indicate the prominent role of human influence on some recent climatic changes. Key Points: New independent evidence of human contribution to recent climatic changes in the lower atmosphere Human influence is detected in global increases in the 500 hPa geopotential height since 1979 A smaller natural signal is also detected in changes of the annual mean geopotential height